2022
DOI: 10.1002/ece3.8705
|View full text |Cite
|
Sign up to set email alerts
|

A pipeline for effectively developing highly polymorphic simple sequence repeats markers based on multi‐sample genomic data

Abstract: Simple sequence repeats (SSRs) are widely used genetic markers in ecology, evolution, and conservation even in the genomics era, while a general limitation to their application is the difficulty of developing polymorphic SSR markers. Next‐generation sequencing (NGS) offers the opportunity for the rapid development of SSRs; however, previous studies developing SSRs using genomic data from only one individual need redundant experiments to test the polymorphisms of SSRs. In this study, we designed a pipeline for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 88 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…SSRs have been the most frequently used genetic marker in population genetics in the past two decades [23]. Recently, Single Nucleotide Polymorphic loci (SNPs) have been used in a variety of genetic studies [24], but they could not replace SSRs completely, even in the genomic era, due to their potential benefits [25]. Multi-allelic nature and high polymorphism of SSR markers help to establish the relationship among the individuals even with fewer markers.…”
Section: Introductionmentioning
confidence: 99%
“…SSRs have been the most frequently used genetic marker in population genetics in the past two decades [23]. Recently, Single Nucleotide Polymorphic loci (SNPs) have been used in a variety of genetic studies [24], but they could not replace SSRs completely, even in the genomic era, due to their potential benefits [25]. Multi-allelic nature and high polymorphism of SSR markers help to establish the relationship among the individuals even with fewer markers.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattarai et al [ 37 ] identified a final set of the 5986 polymorphic SSR loci using the HipSTR program by comparing and counting repeat number variation across the SSR loci of the whole-genome sequence data (30×) among 21 spinach plants. A total of 12,549 SSR loci were genotyped successfully from resequencing data (20×) of 20 brown-eared pheasant individuals using lobSTR software [ 38 ]. Eight hundred and seventy-one polymorphic SSRs were screened across the transcriptome of twelve individuals using the PSR tool in swamp eel [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NGS technologies allow rapid large-scale sequencings at a lesser cost, which permits discovery and development of SSR markers for less studied crops ( Khodaeiaminjan et al., 2018 ; Taheri et al., 2018 ; Luo et al., 2021 ; Wang et al., 2022 ). The genome sequences generated using the NGS technology have been used to discover genome-wide SSRs and develop SSR markers in various tree species, such as pistachio ( Ziya Motalebipour et al., 2016 ), hazelnut ( Öztürk et al., 2018 ), avocado ( Ge et al., 2019 ), fruit and forest species ( Song et al., 2021 ), and Grevillea sp.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the development of microsatellite or SSR markers was an expensive and time-consuming process. But the rapid improvements in sequencing technologies and bioinformatics have reduced the cost and time required for the development of a large set of robust markers through genome sequencing and in silico mining of the genome sequences for potential markers ( Luo et al., 2021 ; Wang et al., 2022 ; Savadi et al., 2023 ). To date, there have been no studies on the genome-wide characterization of microsatellites or SSRs in cashew.…”
Section: Introductionmentioning
confidence: 99%